Criminogenic and Noncriminogenic Needs in Men and Women Who Self-Report Intimate Partner Violence - Radatz, Dana L. (Criminal justice and behavior, 2025)
Little is known regarding the criminogenic needs of men and women who self-report intimate partner violence (IPV). We examined criminogenic and noncriminogenic needs of men and women within the general population who self-reported in three groups: perpetrating physical IPV, perpetrating non-IPV physical violence, and nonviolence perpetration. The sample included 847 men and 1437 women from the Interpersonal Conflict and Resolution (iCOR) Study. Those who self-reported IPV exhibited criminogenic and noncriminogenic needs, ranging from antisocial personality patterns (10%) to criminal associates (69%). Participants who self-reported engaging in IPV had the most criminogenic and noncriminogenic needs, had similar needs to those reporting non-IPV violence, and had consistently more needs than the nonviolence group. Overall, women reported more noncriminogenic needs than men. Community-based IPV treatment programs accepting individuals from multiple referral sources should anticipate variation in criminogenic and noncriminogenic needs among participants, especially relative to gender and referral type.